Mengatasi Stunting melalui Pemberdayaan Komunitas: Inovasi Produk Olahan Ikan dari Kolam AB Banteng KKSS Palangka Raya - Citrariana, Shesanthi; Riani, Defilia Anogra; Ayu, Regina Wahyudyah Sonata; Yosaeunike, Vitatani; Simajuntak, Ruth Riama; Sulistia, Tiya; Fatiqin, Awalul; Alfanaar, Rokiy; Rahman, Sudarman; Febrianto, Yahya; Suprayogi, Thathit; Arsana, Mu'afa Purwa (Bulletin of Community Engagement, 2024)
The community empowerment program which focuses on innovation in processed fish products at the AB Banteng KKSS Palangkaraya Pool aims to overcome the problem of stunting among children by increasing nutritional intake. This initiative utilizes freshwater fish as an abundant source of local protein, by processing them into nutritious products such as nuggets, sausages and fish balls. The method used is the Asset-Based Community Development (ABCD) approach, which identifies and exploits local potential and involves the community in the entire production process. The program results show a significant reduction in the prevalence of stunting from 30% to 18%, an increase in children's daily protein intake from 35 grams to 60 grams, and an increase in average height of 2 cm. This program has also succeeded in increasing community skills and knowledge in fish processing, as well as providing economic benefits through job creation and increased income. Local government support to include processed fish products in school food programs also ensures the sustainability and expansion of program benefits. Challenges faced include changes in eating habits and environmental conditions, which are addressed through intensive nutritional education and pond management training.